Performance Analysis of Interference and Priority aware Coexistence in IEEE 802.15.6 based WBANs - Khan, F.N. (IEEE Computer Society, 2020)
Link/channel scheduling is a process by which different channels within the allowed set of frequencies or different timeslots from a single channel are assigned to achieve minimum interference to the neighbouring nodes and higher efficiency. Existing channel scheduling approaches are often evaluated under the assumption of random mobility model. These approaches tend to average out interfering and non-interfering situations and the end results are not purely applicable to a consistent interference situation, such as the COVID-19 isolation centers. Therefore, in this paper, for a given interference level, we analyze the performance of the Interference and Priority aware Coexistence (IPC) algorithm. To this end, a controlled interference generation model is designed that can ensure consistent interference among a given number of Wireless Body Area Networks (WBANs). The performance is assessed in terms of delay, delivery, reuse, energy consumption, and throughput. Under controlled interference, the results show that the IPC algorithm guarantees better results as compared to existing link scheduling techniques. Â© 2020 IEEE.